Level of Exercise Participation in Individuals with Traumatic Spinal Cord Injury During Inpatient Rehabilitation: A Cross-sectional Study - Adhikari, Shambhu Prasad; Adhikari, Shraddha; Rana, Chanda; Dev, Rubee (Journal of Nepal Health Research Council, 2021)
Background: The outcome of exercises depends on participants’ level of exercise participation. We aimed to investigate the level of exercise participation in individuals with traumatic spinal cord injury during inpatient rehabilitation.Methods: All participants with traumatic spinal cord injury undergoing inpatient physiotherapy at a rehabilitation center were recruited. Participants with hearing/visual problems were excluded. Hopkins Rehabilitation Engagement Rating Scale and Pittsburgh Rehabilitation Participation Scale were used to evaluate exercise participation levels. One-way ANOVA and unpaired t-test were used to compare level of participation between groups. Pearson’s correlation and Chi-square tests were used to evaluate correlation and association. Results: Thirty-five participants with mean age 37.1 ± 11.7 years completed the study. Hopkins Rehabilitation Engagement Rating Scale and Pittsburgh Rehabilitation Participation Scale demonstrated a low level of exercise participation in 31.4 % and 42.9 % participants respectively. Participants with an incomplete injury had high exercise participation levels compared to complete injuries. There were significant group differences (p < 0.001, effect size = 0.8) between complete and incomplete injuries and among various levels of injuries. The level of exercise participation was significantly associated with injury levels and type (p < 0.001, Phi = 0.7 to 0.9). Conclusions: The exercise participation level was high for incomplete compared to complete injuries in Nepalese individuals with traumatic spinal cord injury. The demographic and socio-economical factors were not associated with level of exercise participation.Keywords: Exercise participation; rehabilitation; spinal cord injury